A Brief Patient Self-administered Substance Use Screening Tool for Primary Care: Two-site Validation Study of the Substance Use Brief Screen (SUBS). - McNeely, Jennifer; Strauss, Shiela M; Saitz, Richard; Cleland, Charles M; Palamar, Joseph J; Rotrosen, John; Gourevitch, Marc N (American Journal of Medicine, 2015)
Background: Substance use screening is widely encouraged in health care settings, but the lack of a screening approach that fits easily into clinical workflows has restricted its broad implementation. The Substance Use Brief Screen (SUBS) was developed as a brief, self-administered instrument to identify unhealthy use of tobacco, alcohol, illicit drugs, and prescription drugs. We evaluated the validity and test-retest reliability of the SUBS in adult primary care patients.Methods: Adults aged 18-65 years were enrolled from urban safety net primary care clinics to self-administer the SUBS using touch-screen tablet computers for a test-retest reliability study (n = 54) and a 2-site validation study (n = 586). In the test-retest reliability study, the SUBS was administered twice within a 2-week period. In the validation study, the SUBS was compared with reference standard measures, including self-reported measures and oral fluid drug tests. We measured test-retest reliability and diagnostic accuracy of the SUBS for detection of unhealthy use and substance use disorder for tobacco, alcohol, and drugs (illicit and prescription drug misuse).Results: Test-retest reliability was good or excellent for each substance class. For detection of unhealthy use, the SUBS had sensitivity and specificity of 97.8% (95% confidence interval [CI], 93.7-99.5) and 95.7% (95% CI, 92.4-97.8), respectively, for tobacco; and 85.2% (95% CI, 79.3-89.9) and 77.0% (95% CI, 72.6-81.1) for alcohol. For unhealthy use of illicit or prescription drugs, sensitivity was 82.5% (95% CI, 75.7-88.0) and specificity 91.1% (95% CI, 87.9-93.6). With respect to identifying a substance use disorder, the SUBS had sensitivity and specificity of 100.0% (95% CI, 92.7-100.0) and 72.1% (95% CI, 67.1-76.8) for tobacco; 93.5% (95% CI, 85.5-97.9) and 64.6% (95% CI, 60.2-68.7) for alcohol; and 85.7% (95% CI, 77.2-92.0) and 82.0% (95% CI, 78.2-85.3) for drugs. Analyses of area under the receiver operating curve (AUC) indicated good discrimination (AUC 0.74-0.97) for all substance classes. Assistance in completing the SUBS was requested by 11% of participants.Conclusions: The SUBS was feasible for self-administration and generated valid results in a diverse primary care patient population. The 4-item SUBS can be recommended for primary care settings that are seeking to implement substance use screening.